KONSTRUKSI NILAI-NILAI KESETARAAN GENDER DALAM BUKU SUARAKU EKSPRESIKU KARYA NURUL ILMI IDRUS - Haruna, Rahmawati (Jurnal Berita Sosial, 2018)
This study aims to answer the question of how the form of gender equality resistance described by Nurul Ilmi Idrus in my Suaraku Ekspres Book through the analysis of the discourse of Teun A. Van Djik model. Based on research focus and methodological aspects, the type of research used is qualitative research because it is considered relevant as a research method to analyze a problem about the construction of gender equality values in my Suaraku Ekspres Book written by Nurul Ilmi Idrus. The research location of the researcher is more unbound because it is a literature research. The time used in this research process is two months from November to January 2018. The approach in this research is the approach of study of discourse analysis of Teun A. Van Djik model, that is approach which see text factor as important element in discourse. Based on the result of this research is the construction of gender equality values in the book Suaraku Eskpresiku by Nurul Imi Idrus it can be concluded that the form of gender equality is divided into three forms, namely; First, the form of gender equality in education where men and women have equal opportunities to get a decent education. Second, the form of gender equality in the household. Thirdly, the form of gender equality in social society ie Men and women alike have equal opportunity to enter into organization, to lead a mass media, have rights in conveying ideas, thoughts related to social condition of society